Penggunaan Bang Ruli Berbantuan LKS untuk Meningkatkan Prestasi Belajar Siswa Sekolah Menengah Pertama - Harna Yulistiyarini (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the eighth grade students’ learning outcomes in geometry through Bang Ruli media in Junior Secondary School 1 Dukuhseri, Pati District. This research was designed using a Research and Development model with needs analysis, designing , developing, validating, and trying out using a classroom action scheme. Data were collected through observation on learning and test on the students’ learning outcomes. Data were analyzed descriptively, quantitatively and qualitatively. Research resulted in development of Bang Ruli practical and multifunction media for learning geometry. The implementation of such media could facilitate students’ learning from 48% in pre-cycle to 85% in cycle 2, and 88% in cycle 2. Moreover, the students’ learning outcomes improved from 23% in precycle to 59 in cycle 1 and 86% in cycle 2.